Continuous professional development: Assessing teachers' experiences with the cascading training model - Hugh Leong; Souba Rethinasamy (Journal of English Language Teaching Innovations and Materials (Jeltim), 2023)
Continuous professional development (CPD) is integral in educational reform; developing and enhancing teachers’ pedagogical skills and knowledge. In Malaysia, the cascade training model is often preferred for CPD programmes in public secondary schools. This may be due to cost effectiveness and reach, where many teachers can be trained in a short timeframe. Critics of the cascade model of training tend however, point to a risk of knowledge being diluted as it is transferred from the trainers to the attendees and then to teachers in schools. This paper focuses on documenting the experiences of Malaysian secondary school English teachers attending school-based assessment (SBA) CPD training courses using the cascade training model. Adopting a qualitative research approach, through the use of in-depth semi-structured interviews, data was collected from 14 English teachers from 14 public secondary schools. The findings indicate that there were mixed experiences of teachers attending cascade training programs and that of subsequent trainings that were conducted by attendees of the programmes. These experiences were affected largely by the quality of the training programme (i.e. design of program curriculum and materials), trainer quality, participants selected, and follow up support afforded to participants. This paper culminates with recommendations for further CPD improvements.